Regulatory Cycles : Revisiting the Political Economy of Financial Crises - Dagher, Jihad (IMF Working Papers; Working Paper ;, 2018)
Financial crises are traditionally analyzed as purely economic phenomena. The political economy of financial booms and busts remains both under-emphasized and limited to isolated episodes. This paper examines the political economy of financial policy during ten of the most infamous financial booms and busts since the 18th century, and presents consistent evidence of pro-cyclical regulatory policies by governments. Financial booms, and risk-taking during these episodes, were often amplified by political regulatory stimuli, credit subsidies, and an increasing light-touch approach to financial supervision. The regulatory backlash that ensues from financial crises can only be understood in the context of the deep political ramifications of these crises. Post-crisis regulations do not always survive the following boom. The interplay between politics and financial policy over these cycles deserves further attention. History suggests that politics can be the undoing of macro-prudential regulations.